”Os Eden er igen oplukt”. Kerubmotivet i luthersk kirkekunst genovervejet - Bach-Nielsen, Carsten (Hikuin, 2017)
“To Us Eden was Reopened”. The cherub motif in Lutheran church art reconsidered By Carsten Bach-Nielsen The fall of man (Gen 3) is a motif hardly ever met in Danish medieval sculpture. After the Reformation however it occurs frequently on pulpits and more significant on altarpieces. This probably is caused by Martin Luther’s and the Lutheran reformers’ concept of redemption and grace – and the new stress on confession as a prerequisite for joining in the communion. A number of post-reformation altar decorations display the fall with Adam’s and Eve’s picking of and consumption of the forbidden fruit – together with the Christian promise of return due to Christ’s victory over devil and death. Return to what, one might ask. – To Eden, to Heaven, to the inner of Solomon’s temple, to grace? In the 17th and the 18th centuries the return to and through the gates of Heaven is staged by means of railings separating the choir form the nave of the churches. In the wooden sculpture of Eastern Jutland the railings are often turned into dramatic scenes of exclusion and inclusion by means of life size cherubs guarding the gates with their flaming swords. The railings may have been furnished with written and painted scores for an imagined conversation between the guarding angelic figures and the living users of the church. Here the confession of sin is expressed together with the formulation of Christ’s promises. The cherubs are supposed to listen and answer, but the can only communicate to us by means of replies painted on the doors or railings; so there is a zone of discussion concerning grace and the gifts of grace established at the important liminal zone between the two parts of the church. This zone offers a scene for the reenactment of the narrative, the expulsion of Eden – and for the proclamation of the promise of reintroduction to the garden. These arrangements obviously have to do with the rituals and ceremonies of confession, not least the ones related to the public confession. This rite since the 17th century was staged at the doors between the nave and the choir; here the repentant sinner was supposed to kneel before he would be reintegrated into the congregation and was again accepted as partaker in the Holy Communion. The kneeling figures of Adam and Eve that are seen on a number of such railings may mirror the penitent Christians in the ritual of confession. The cherubs may also be seen in the light of classical ekfrasis, descriptions of buildings used to recreate or copy buildings of the past. The Book of Kings contains vast descriptions of the inner and most holy of the Temple of Jerusalem. Here cherubs were part of an all-covering decoration. Constructing new rooms for the church service in the era of Lutheran orthodoxy required knowledge of the most significant building in Christian narrative, The Jerusalem Temple. The cherubs and the railings have a twofold meaning as staging a way back to innocence or grace – and as a restaging of the Jerusalem Temple with its concentrated holiness and presence of divine power. The staged discussions between man and angel bears a resemblance to a well-known and quite popular motif in the post-reformation church, namely the litigatio sororum, Adam and Eve before the court of Trinity. Here the scene is set in court by a cherub who offers the fallen couple four skilled with defenders. It all has to do with the arguments permitting the sinners to make their way back to full grace. The scene is painted as a mural in the church of Tullebølle on the isle of Langeland. Danish Grundtvigian and liberal artist Joakim Skovgaard in 1890 painted an altarpiece for the tiny church of Mandø in the North Sea. He chose his point of departure in the apocryphal gospel of Nicodemus. Here Christ leads the thief, who was convinced and conversed in the last minutes of his life, into the Garden of Eden. The painting depicts a 169 huge wall guarded by a Florentine renaissance angel – and the thief received by angels on the fair lawns of Paradise. The entrance to Paradise is not a problem to any Christian no matter how late he may have come to faith. Somewhat different is the ideology behind the decorative programs of the churches of the Copenhagen Church Building Society. Sculptor Thomas Bærentsen in 1904 chose to show Adam and the Cherub on the baptismal front facing the congregation in the nave while he depicted the baptism of Christ on the side fronting the altar of the church. So he managed to make a new distinction or demarcation line between the “high” church of true believers – and the “low” nave of more ordinary Christians.